2023
DOI: 10.3390/jcm12154958
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Analysis in the Prediction of Occult Lymph Node Metastases in Patients with Oral Cancer: A Systematic Review

Abstract: Background: Tumor extension and metastatic cervical lymph nodes’ (LNs) number and dimensions are major prognostic factors in patients with oral squamous cell carcinoma (OSCC). Radiomics-based models are being integrated into clinical practice in the prediction of LN status prior to surgery in order to optimize the treatment, yet their value is still debated. Methods: A systematic review of the literature was conducted according to the PRISMA guideline. Baseline study characteristics, and methodological items w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Although not used in this study, MRI diffusion-weighted imaging and apparent diffusion coefficient may add new diagnostic criteria [42]. In recent years, research on diagnosing lymph nodes using artificial intelligence and radiomics has been reported, and this may be useful in diagnosing lymph node metastasis in the future [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Although not used in this study, MRI diffusion-weighted imaging and apparent diffusion coefficient may add new diagnostic criteria [42]. In recent years, research on diagnosing lymph nodes using artificial intelligence and radiomics has been reported, and this may be useful in diagnosing lymph node metastasis in the future [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that apply negative palpation to define N0 neck may have a higher sensitivity than those that apply a more sophisticated assessment with prospective staging techniques. The method of MRI examination was adopted in this study ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be an increase risk in head and neck cancers when cervical lymph node disease is untreated, some reasons support withholding cervical lymph node treatment. A significant portion of patients experience a decrease in quality of life (shoulder dysfunction, for example) and needless medical expenses (22)(23)(24). Additionally, the cancer growth could be effected by this additional treatment.…”
Section: Although the Use Of Imaging Techniques In A Clinical Suspicionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, we have observed an increasing trend of publications on radiomic approaches in oncology [11], especially for predicting diagnosis [12][13][14] and treatment response [15][16][17][18][19], as well as tumor molecular profiles [20,21]. In particular, in patients with HNSCC, different radiomic features extracted from computed tomography (CT) imaging, which is routinely performed in this setting, were significantly associated with clinical (local control, tumor failure, lymph node metastasis, extranodal extension, overall survival, human papillomavirus (HPV) status) and histological (differentiation grade, perineural and lymphovascular invasion) parameters as well as molecular features, especially some specific somatic mutations, in patients with head and neck cancer [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%